Individual, relational, and contextual dynamics of emotions - Petitta, Laura; Härtel, Charmine E. J., 1959-; Ashkanasy, Neal M., 1945-; Zerbe, W. J. (Research on emotion in organizations ;, 2018)
This volume of 'Research on Emotions in Organizations' contributes to the ongoing study of the emotion-related forces that shape the functioning of individual, interpersonal workplace relationships and the organizational system as a whole. The chapters in this book demonstrate the complex interplay between emotion, cognitive processes, brain functioning and contextual factors that contribute to a better understanding of organizational behavior at multiple levels of workplace life and in the context of a fast-paced, uncertain and dynamically changing work environment. Taken together, they provide recent advances on the dynamics of emotions and point to future research venues consistent with the increasing interest in cross-country investigation and the role of neuroscience in organizational psychology. This volume is organized in three parts to provide coverage of the latest developments in each of the following areas: micro-level self-related dynamics of emotions; relational-centered dynamics of emotions; and emotional dynamics related to macro contextual factors.